The Effect of Mental Toughness of Individuals Doing Outdoor Sports on their Decision-Making Skills - Esra Canlı; Burak Gürer; Enise Merve Karababa (Türk Spor ve Egzersiz Dergisi)
This study intends to examine the impact of the mental toughness of athletes doing outdoor sports on their decision-making skills. The study population is composed of 504 athletes doing outdoor sports in various disciplines in Turkey in 2017. The mental toughness in sports scale developed by Sheard et al. (2009) and adapted to Turkish by Altıntaş and Bayar Koruç (2016) and the Melbourne Decision Making Scale I-II Scale developed by Mann et al. (1998) and adapted to Turkish by Deniz (2004) were used. The Independent Samples T test was used to analyze the data obtained as well as the One Way Analysis of Variance (One Way Anova) used in case of the existence of more than two groups and the correlation analysis for the relationship between the two groups. As a result, significant differences were found by the variables gender, marital status, age, educational status, the type of outdoor sports engaged in and experience. Accordingly, mental toughness has effects on decision-making skills when doing outdoor sports. There is a low level of positive correlation between mental toughness and decision-making skills. It is thought that the seasons and the types of outdoor sports done have an impact on these results.